THE EFFECT OF TEACHING MEDIA AND EMOTIONAL INTELIGENT ON STUDENTS’ SPEAKING SKILL - astati, era (Jurnal Curricula, 2017)
This research aimed at finding the effects of teaching media and emotional intelligence on students’ speaking skill. The research is an experimental research involving 40 students in STIKes YPAK Padang. The data were collected by giving the students a speaking performance test and a questionnaire of emotional intelligence. The data was analyzed by using two ways analysis of variance (ANOVA 2x2). Before doing the analysis, the data normality was tested by using Kolmogorov-Smirnov test to see if the population where the sample was taken had normal distribution. The result of the research concluded: (1) Teaching media gives a significant effect on the students’ speaking skill. Test result obtained that p-value for category teaching media is 0,008 < 0,05 and F observe 7,931. (2) Emotional intelligence gives a significant effect on the students’ speaking skill in STIKes YPAK Padang. The result obtained that p-value for emotional intelligence is 0,000 < 0,05 and F observe 40,458. (3) Teaching media and emotional intelligence give significant interaction effects of students’ speaking skill. Test result retrieved that p-value for category of teaching media and emotional intelligence is 0,010 < 0,05 and F observe 7,393.